1995
DOI: 10.1073/pnas.92.6.2096
|View full text |Cite
|
Sign up to set email alerts
|

OR-1, a member of the nuclear receptor superfamily that interacts with the 9-cis-retinoic acid receptor.

Abstract: We have cloned a member of the nuclear receptor superfamily. The cDNA was isolated from a rat liver library and encodes a protein of 446 aa with a predicted mass of 50 kDa. This clone (OR-1) shows no striking homology to any known member of the steroid/thyroid hormone receptor superfamily. The most related receptor is the ecdysone receptor and the highest homologies represent <10%v in the amino-terminal domain, between 15-37% in the carboxyl-terminal domain and 50-62% in the DNA binding domain. The expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
137
0
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(144 citation statements)
references
References 35 publications
5
137
0
2
Order By: Relevance
“…LXR␣ and the closely related orphan receptor LXR␤ are broadly expressed and bind to DNA as heterodimers with the retinoid X receptors (RXRs) (11)(12)(13)(14). As part of an effort to identify natural LXR ligands, we have found that the oxysterols 24(S),25-epoxycholesterol and 24(S)-hydroxycholesterol activate both LXR␣ and LXR␤ at concentrations consistent with those found in tissue extracts.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…LXR␣ and the closely related orphan receptor LXR␤ are broadly expressed and bind to DNA as heterodimers with the retinoid X receptors (RXRs) (11)(12)(13)(14). As part of an effort to identify natural LXR ligands, we have found that the oxysterols 24(S),25-epoxycholesterol and 24(S)-hydroxycholesterol activate both LXR␣ and LXR␤ at concentrations consistent with those found in tissue extracts.…”
mentioning
confidence: 83%
“…We note that both LXRs are expressed in the liver. Interestingly, Northern analyses have demonstrated that LXR␤ is expressed in the brain (14). More detailed in situ studies have shown that LXR␤ is broadly expressed in fetal brain and that its expression becomes more restricted in postnatal and adult brains (26).…”
Section: Oxysterols Activate the Lxr Nuclear Receptors 3139mentioning
confidence: 99%
See 1 more Smart Citation
“…LXR␣ and LXR␤ are members of the nuclear receptor supergene family of ligand-activated transcription factors (22,23). Their endogenous ligands are oxysterols (24,25).…”
mentioning
confidence: 99%
“…Finally, RXRs may also be the heterodimeric partners of a number of orphan nuclear receptors, including members of the FXR/RLD-1/LXR/UR family (Apfel et al 1994;Song et al 1994;Forman et al 1995a;Seol et al 1995;Teboul et al 1995;Willy et al 1995; note that UR has also been named OR-1 or RIP15), members of the NGFI-B/ NURR-1 family (Forman et al 1995b;Perlmann and Jansson 1995), and the orphan receptor MB67 (Baes et al 1994).…”
mentioning
confidence: 99%